Ovarian perforation in polycystic ovary syndrome: long-term pregnancy rate - صالح حسن (Latakia University Journal -Medical Sciences Series, 2022)
Objective: To report long term pregnancy rate in polycystic ovary syndrome (PCOS) treated by ovarian drilling. To evaluate predictive factors of pregnancy and possibility of a second drilling. Design: Retrospective, observational, multicenter study. Setting: Gynecologic departments of two teaching’s hospitals. Patients: All infertile women with PCOS who were treated by ovarian drilling from 2004 to 2013. The Rotterdam criteria were applied to define PCOS. Intervention(s): Surgical ovarian drilling by laparoscopy and trans vaginal hydro laparoscopy. Main Outcome Measure(s): The primary endpoint was pregnancy rate after ovarian drilling. The secondary endpoints were the predictive factors of pregnancy and the possibility of a second ovarian drilling. Results: 289 women were included in the study. The mean follow-up period was 28.4 months (25.3–31.5).A pregnancy was obtained in at least 137 (47.4%) women after a drilling, and 71 (51.8%) of thesepregnancies were spontaneous, 48 (16.6%) women achieved atleasttwo pregnancies after drilling, and 27(56.3%) of these were spontaneous. The predictive factors for effectiveness were a normal body mass index (BMI), an infertility period of less than three years, an AFC of less than 50, and an age of less than 35. Second drillings were performed on 33 women. Among them,19 (57.6%) achieved at least one pregnancy, and 10 (52.6%) of these were spontaneous. It appeared that a second drilling was effective either when the first drilling had been successful (pregnancy achieved after drilling) or when it had failed in cases ofhigh AFC (greater than 55( Conclusion: Ovarian drilling permitted to obtain spontaneous pregnancy for women with PCOS. This surgery could have durably effect permitted to obtain more than one pregnancy.